Correlation between ferroelectricity and nitrogen incorporation of undoped hafnium dioxide thin films. (June 2020) - Luo, Jun-Dao; Yeh, Yun-Tien; Lai, Yu-Ying; Wu, Chia-Feng; Chung, Hao-Tung; Li, Yi-Shao; Chuang, Kai-Chi; Li, Wei-Shuo; Chen, Pin-Guang; Lee, Min-Hung; Cheng, Huang-Chung
Abstract: The ferroelectric characteristics of undoped hafnium oxide (HfO2 ) in titanium nitride (TiN)/HfO2 /TiN stacks exhibited improved remanent polarization by controlling the nitrogen gas flow during TiN deposition in this work. Electrical measurements revealed that samples with a higher N2 /(Ar + N2 ) ratio obtained a higher remanent polarization of approximately 10 μC/cm 2 at 2.5 V but exhibited a larger leakage current and less reliability. Among all the samples, the sample with a N2 /(Ar + N2 ) ratio of 33% exhibited a relatively high remanent polarization of 12 μC/cm 2 and excellent endurance over 10 8 cycles. Through X-ray photoelectron spectroscopy (XPS) analysis, it was observed that increasing the N2 gas flow during TiN electrode deposition contributed to excessive N-diffusion, leading to the creation of more oxygen vacancies and subsequently to device failure. Therefore, controlling the appropriate N2 gas flow during TiN deposition is crucial to enhance the ferroelectric characteristics of undoped HfO2 . The results of this study may be applicable to future work on nonvolatile memory applications. Highlights: Enhancing ferroelectricity in undoped-HfO2 was investigated via controlling the nitrogen gas flow during TiN deposition. An excellent endurance can be sustained over 10 8 cycles under 3.75 MV in undoped-HfO2 memory. Controlling the appropriate N2 gas ratio during TiN electrode deposition was improved the ferroelectric properties.